Running into fatigue: The effects of footwear on kinematics, kinetics, and energetics - Sanno, M.; Epro, G.; Brüggemann, G.-P.; Willwacher, S. (Medicine & Science in Sports & Exercise, 2021)
Purpose: Recent studies identified a redistribution of positive mechanical work from distal to proximal joints during prolonged runs, which might partly explain the reduced running economy observed with running-induced fatigue. Higher mechanical demand of plantar flexor muscle-tendon units, for example, through minimal footwear, can lead to an earlier onset of fatigue, which might affect the redistribution of lower extremity joint work during prolonged runs. Therefore, the purpose of this study was to examine the effects of a racing flat and cushioned running shoe on the joint-specific contributions to lower extremity joint work during a prolonged fatiguing run. Methods: On different days, 18 runners performed two 10-km runs with near-maximal effort in a racing flat and a cushioned shoe on an instrumented treadmill synchronized with a motion capture system. Joint kinetics and kinematics were calculated at 13 predetermined distances throughout the run. The effects of shoes, distance, and their interaction were analyzed using a two-factor repeated-measures ANOVA. Results: For both shoes, we found a redistribution of positive joint work from the ankle (-6%) to the knee (+3%) and the hip (+3%) throughout the entire run. Negative ankle joint work was higher (P < 0.01) with the racing flat compared with the cushioned shoe. Initial differences in foot strike patterns between shoes disappeared after 2 km of running distance. Conclusions: Irrespective of the shoe design, alterations in the running mechanics occurred in the first 2 km of the run, which might be attributed to the existence of a habituation rather than fatigue effect. Although we did not find a difference between shoes in the fatigue-related redistribution of joint work from distal to more proximal joints, more systematical studies are needed to explore the effects of specific footwear design features.